Pengaruh Konsep Diri dan Kecemasan Siswa Terhadap Pemahaman Konsep Matematika - Shinta Dwi Handayani (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
This research was conducted with the purpose of knowing the self concept and anxiety influence students towards an understanding of mathematical concepts. The methods used in this research is a survey method. Affordable population are students of Class XI Science social sciences academic year 2014/2015 in Depok. Large sample as much as 90 students, with a sampling technique used was a combination of proportional and random, taken from three private schools. Research instrument used, namely the now self concept as much as 37 statement, now as many as 36 students anxiety statements, test understanding math concepts shaped 24 multiple choice question, which has been in test validitasnya. Data analysis using path analysis. The results of hypothesis testing indicate that: 1) there is a significant direct influence on the concept itself against the understanding of mathematical concepts. 2) there is a significant direct influence on anxiety of students towards an understanding of mathematical concepts. 3) there is a significant direct influence on the concept of yourself against anxiety students. 4) there is an indirect influence on the concept of understanding the mathematical concepts themselves against through the anxiety of students. Keywords: self concept, to the dismay of the students, understanding of math concepts.